Integrated Approach for Management OF Supply chain and relationship with MRP - يوسف نغم; خلف بتول عطية; صبيح بشرى (Journal of Economics and Administrative Sciences, 2012)
Find interested in the harmonization of variables and determinants of supply chain planning needs of the material, leading to the results start effective supply chain management, and end up quickly modify the sizes to suit the demand and turnover in the market. As well as identifying relationships between variables, and type of relationship used by the company with the processors and their feasibility, and indicate the level of interest and willingness to redesign the supply chain Company for Electrical Industries and build an integrated model for supply chain with the MRP system can be applied in the company. Research depend on quantitative and descriptive method, It was based manner quantitative to quantitative data from the reality of the company, and measured the laws of a particular show specific results, while the used the descriptive method for realizing the existence of the problem the company examined, as were polled a number of administrators and technicians opinion working in departments stores and procurement exclusively through the checklist (check list), which showed a real problem in the General Company for Electrical Industries in the form of increasing the size of inventories of raw materials and semi-manufactured parts in addition to a gap between the times from receiving such materials from suppliers and the time needed.